A study on the barriers to Anti-retroviral Therapy adherence among Human Immunodeficiency Virus infected adolescents in Gaborone (Botswana) - Ndiaye, Maimouna (My University, 2012)
Introduction: Barriers associated with good adherence to Antiretroviral Therapy (ART) among human immunodeficiency virus (HIV) infected adolescents are multiple and complex. Those barriers contribute to low adherence levels putting infected adolescents at risk of developing resistance and decreasing their survival time. Patients care givers psychosocial and demographic variables, medication related factors and health care delivering factors are among the barriers that correlate with non adherence to antiretroviral drugs (ART’s) among HIV infected adolescents. Those barriers vary across individuals within the same population of adolescents. This study was conducted to determine the level of adherence among HIV infected adolescents on ART and to identify barriers associated with non adherence among this population attending the Botswana Baylor Children’s Clinical Center of Excellence (COE) in Gaborone, Botswana. Materials and methods: A cross sectional analytical study using quantitative data was performed. A structured, self administrated questionnaire adapted from the AIDS Clinical Trials Group (ACTG) was used to identify the barriers while the socio-demographic and clinical data were retrieved from study participants’ medical records. The adherence level was estimated using the pharmacy pill count technique. The adolescents aged 13 to 18 years receiving ART for more than 6 months and attending the ART National Program at the time of the study and who did assent and had their care givers consent to participate in the study were included in the analysis. Results: A high adherence level (75.6%) was reported among the study participants. Besides gender, no other socio-demographic and clinical variables showed association with non adherence. Male adolescents were found to be 70% less likely to adhere to their medication than their counterpart females [p= 0.020, OR=0.30, 95% CI (0.10 – 0.85)]. Furthermore adolescents v who missed a dose because their pills were not collected from the pharmacy either by themselves or by their care givers were 77 % less likely to adhere to their ART medication than those who did not miss a dose because they had their medication collected [p= 0.019, OR= 0.23, 95%CI (0.064 – 0.837)]. Conclusion: A high proportion of HIV infected adolescents attending the Baylor Center of Excellence ART National Program were adherent to their medication. Despite the high level adherence to ART among this age group, interventions to improve adherence level should be designed with a focus on male adolescents and to reinforce counseling of care givers and adolescents about the hazards of poor adherence to treatment. Further research is however, needed to elucidate more about the two main barriers that were found to be significantly associated with non adherence among adolescents at Botswana Baylor Children’s Clinical Center of Excellence: male-gender and medication collection from the pharmacy.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Masters of Public Health in the field of Health Measurement 22nd February, 2012
Keywords: HIV; Antiretroviral Therapy, Highly Active